Immunoprocedures for detecting human chorionic gonadotropin: clinical aspects and doping control - Stenman, U. -H.; Unkila-Kallio, L.; Korhonen, J.; Alfthan, H. (Clinical Chemistry, 1997)
The pregnancy hormone human chorionic gonadotropin (hCG) is also present at low concentrations in plasma and urine of men and nonpregnant women. hCG immunoreactivity occurs in various molecular forms: Besides the intact hCG heterodimer, considerable amounts of proteolytically cleaved forms, free subunits, and fragments are found in plasma and urine. Especially in urine, proteolytic fragments constitute a major part of the hCG immunoreactivity. The different forms of hCG cross-react to various degrees in immunoassays and constitute a problem for standardization of specific hCG determinations. After injection of hCG (10 000 IU of Pregnyl®; Organon), above-normal concentrations of hCG can be detected in serum and urine for 7-11 days. Most immunoassays for hCG also measure hCGß. Quantitative hCG determinations are mainly performed on serum samples, and very few commercial hCG determinations have been validated for determination of urine samples. Considerable care must therefore be exercised when utilizing such assays to analyze urines for doping control.